2016
DOI: 10.1038/srep36295
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental Divergence and the Value of Control

Abstract: A critical aspect of flexible choice is that alternative actions yield distinct consequences: Only when available action alternatives produce distinct outcome states does discrimination and selection between actions allow an agent to flexibly obtain the currently most desired outcome. Here, we use instrumental divergence – the degree to which alternative actions differ with respect to their outcome probability distributions – as an index of flexible instrumental control, and assess the influence of this novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…These findings suggest that dopamine signals targeting areas in the striatum may be important for reinforcing the preference for control. Additionally, a recent study demonstrated that a preference for free choice was more pronounced in case of high instrumental divergence (i.e., when choices differ more with respect to their outcome probability distributions) (Mistry and Liljeholm, 2016). Thus, the preference for free choice was higher when choices have a more meaningful impact on outcome.…”
Section: Instrumental Contingency Shapes Controllabilitymentioning
confidence: 99%
“…These findings suggest that dopamine signals targeting areas in the striatum may be important for reinforcing the preference for control. Additionally, a recent study demonstrated that a preference for free choice was more pronounced in case of high instrumental divergence (i.e., when choices differ more with respect to their outcome probability distributions) (Mistry and Liljeholm, 2016). Thus, the preference for free choice was higher when choices have a more meaningful impact on outcome.…”
Section: Instrumental Contingency Shapes Controllabilitymentioning
confidence: 99%
“…Experimental design and statistical analysis Task and procedure. Participants were scanned with fMRI while performing a simple gambling task, illustrated in Figure 1 and described in detail by Mistry and Liljeholm (2016). At the start of the experiment, participants were instructed that they would assume the role of a gambler in a casino, playing a set of four slot machines (labeled A1, A2, A3, and A4, respectively) that yielded three different colored tokens (blue, green, and red), each worth a particular amount of money, with different probabilities.…”
Section: Methodsmentioning
confidence: 99%
“…A series of recent studies (Mistry and Liljeholm, 2016;Liljeholm et al, 2018) have demonstrated that individuals prefer environments in which instrumental divergence, the degree to which alternative actions differ with respect to their outcome probability distributions, is relatively high. A high level of instrumental divergence is a necessary feature of flexible instrumental control: If all available action alternatives have identical, or very similar, outcome distributions, such that selecting one action over another does not significantly alter the probability of any given outcome state, an agent's ability to exert control over its environment is considerably impaired.…”
Section: Introductionmentioning
confidence: 99%
“…In the counterfactual literature, models of causal reasoning (e.g., Pearl, 2000) share this idea with modern instantiations of the associative approach, such as recent accounts based on experienced action-outcome contingency -where contingency is defined as the difference between conditional probabilities, such as the so-called "ΔP rule" (e.g., Tanaka, Balleine and O'Doherty, 2008) -and with model-based learning algorithms drawing upon the notion of instrumental divergence (i.e., "Jensen-Shannon divergence"). Instrumental divergence formalizes the causal power of an action as the difference between probabilities of a given outcome in the presence vs. absence of this action (Liljeholm et al, 2011;Liljeholm et al, 2013;Mistry and Liljeholm, 2016). Interestingly, both counterfactual reasoning and instrumental divergence are endowed with the same prior belief about goal-directed actions.…”
Section: Counterfactual Models: Causation Is About Actions That Make mentioning
confidence: 99%
“…CF studies have provided convincing evidence that people generate counterfactuals when reasoning about causation (Sloman and Lagnado, 2015, for a review), whereas instrumental divergence provides a learning rule for how people make choices based on maximized divergence (Mistry & Liljeholm, 2016). However, both views have shortcomings.…”
Section: Overview Of the Present Studymentioning
confidence: 99%